2020
DOI: 10.1016/j.ijnonlinmec.2020.103559
|View full text |Cite
|
Sign up to set email alerts
|

Design, analysis and experimental validation of high static and low dynamic stiffness mounts based on target force curves

Abstract: In order to improve vibration isolation, soft components can be used in engineering applications, but this can lead to excessive static deflection. An ideal vibration isolator should have a high static stiffness to ensure that it has sufficient load carrying capacity; at the same time, it should have a low dynamic stiffness to maximize the vibration isolation frequency range. Recently, high static and low dynamic stiffness (HSLDS) mounts have been increasingly shown to have significant benefits for various eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The best controller, according to the results, is ANIPPF. Sun et al [15] determined the displacement transmissibility under harmonic excitation by analyzing the dynamics of a system based on the nth-order HSLDS mounts using the average approach. The findings demonstrated that improving the damping ratio in a suitable manner improves the HSLDS mount's isolation capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The best controller, according to the results, is ANIPPF. Sun et al [15] determined the displacement transmissibility under harmonic excitation by analyzing the dynamics of a system based on the nth-order HSLDS mounts using the average approach. The findings demonstrated that improving the damping ratio in a suitable manner improves the HSLDS mount's isolation capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [12][13][14] studied an orthogonal six-degree-of-freedom vibration isolation system with HSLDS and an electromagnetic Stewart platform to suppress the low-frequency vibration of high-precision instruments, provided modal coefficients by improved Fourier series and the Rayleigh-Ritz method, and studied the nonlinear energy transfer of flexible plates with arbitrary boundaries coupled to HSLDS isolators. Sun et al [15] proposed a method for designing HSLDS mounts based on target force curves, which are obtained by placing negative stiffness structures in parallel with positive stiffness linear springs. Yao et al [16] proposed an HSLDS isolator with a cam-roller-spring mechanism, in which the cam profile can be specially designed to suit different operating requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al proposed a cam-roller-spring QZS mechanism with n-order stiffness behavior. Compared with the low-order QZS devices, the mechanism had lower dynamic stiffness near the equilibrium position and better vibration isolation effect (Sun et al, 2020). Bian et al reported a novel tunable and nonlinear QZS vibration isolation device based on the X-shaped structure.…”
Section: Introductionmentioning
confidence: 99%